Community Foudations: main characteristics and trends – A comparison between Islamic Republic of Iran and Italy - Maggi, Davide; Rossi, Noemi; Faiznia, Mazdak; Houshmand, Hirad (European Journal of Islamic Finance, 2019)
The following document presents the ethical, cultural roots of Community Foundations. The paper starts from a historical framework of the word foundation. Understanding the etymology of the word foundations, one understands his mission and his philosophy. This document takes the example of the Italian Community Foundations and explains the origin of it, how they were born in Italy, which fields are covered and the dynamics between the various actors. The same analysis is made for the non-governmental and non-profit organisations in Iran. To fully comprehend the Iranian reality an analysis is necessary to describe the two different periods, before and after the 1979 revolution. In conclusion, the paper demonstrates how important community foundations are to be tested, especially in this period of great economic difficulty.